Edukasi Bertanam Sayur pada Anak-anak Usia Sekolah menggunakan Pemanfaatan Barang Bekas sebagai Sarana Hidroponik Statis di Desa Pagarawan - Khodijah, Nyayu Siti; Septianti, Bella; Santi, Ratna; Wahyuni, Winda; Minawati; Aquarina, Ririn (Indra Institute Research & Publication, 2022)
KKN during the pandemic had many challenges, one of which was the existence of school-aged children who were more conditioned to study at home. One of the activities initiated was the education of school-age children by planting simple hydroponic vegetables using used goods. The main purpose of this activity is to increase creativity and care for the environment for school-age children in Pagarawan Village, by teaching that hydroponic vegetable farming can be done with simple methods, tools and materials. The specific goal is to help increase the knowledge of the Pagarawan community in cultivating vegetables that can be done simply without using large areas of land, spending a lot and producing higher quality and more satisfying results. Method This activity begins with outreach to school-age children in Pagarawan Village and hands-on practice. The results of the activity were in the form of an introduction to simple hydroponic vegetable growing activities for school-age children, to fill the learning period during a pandemic.